Partial Rotator Cuff Tear outcome between prolotherapy with physical rehabilitation compared to physical rehabilitation only: A Meta-analysis approach - Galuh Ayu Ratna Savitri; Thomas Erwin Christian Junus Huwae (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2023)
Partial Tear Rotator Cuff Tendinopathy (PTRCT) impacts 15% to 50% of the population and increases in prevalence with individuals' age. Several first-line management strategies for treating rotator cuff disease, such as physical rehabilitation and/or injection, have been reported. However, optimum management is debatable. This study aims to explore the outcome management combination of prolotherapy and physical rehabilitation with physical rehabilitation only for PTRCT. Randomized Control Trial (RCT) studies From PubMed, Cochrane Library, ScienceDirect, ProQuest, And Google Scholar were included. Two independent reviewers evaluated the quality of RCTs using the Cochrane Risk of Bias Tool. The primary result was pain reduction, with functional improvement as a secondary outcome. Meta-analysis was performed using Review Manager 5.4 software. Our meta-analysis included 5 RCT studies involving 263 patients. Standardized mean difference (SMD) was collected from all of the studies. In this study, pain reduction was significantly decreased in the prolotherapy group compared with physical rehabilitation only during 12 weeks follow-up (-0.97 (95% -1.63 to -0.31) with p: 0.0004) and obtained I2Â 57 % that, representing moderate heterogeneity. In contrast, Functional improvement did not significantly reduce (-1.04 (95% -5.45 to 3.317) with p: 0.64. In conclusion, Prolotherapy with physical rehabilitation can reduce pain in long-term (12 weeks) patients with PTRCT compared to physical rehabilitation only but give no significant effect in improving functional outcomes.